Teknik för vårskörd av hampa till stråbränsle - Olsson, Mattias; Nilsson, Johannes (2008)
Hemp is an annual energy crop that fits very well in Swedish crop rotations. It is an interesting crop with many benefits, for example its ability to establish a large quantity of biomass in one year. Hemp is easy to grow and out-competes unwanted weeds through its aggressive growth pattern without the need for pesticides. Interest in growing hemp and other energy crops is currently decreasing, apparently because of high grain prices. These high prices give a higher net profit that we believe could partly cover the cost of hemp cultivation, while the hemp in turn would improve the crop rotation and thus repay its debts in the form of increased yields of other crops. The great disadvantage of hemp is the lack of knowledge about spring harvest of the crop. Spring harvest of hemp as straw fuel produces benefits in combustion quality but appears to generate large field losses of biomass that have not yet been accounted for. A satisfactory technique exists for autumn harvest of green hemp for biogas production. In this study we carried out field tests to measure harvesting losses in a hemp field close to Lund, southern Sweden. The hemp was cut using a modified (rapeseed) windrower or a forage harvester with a modified header that lays the material on the ground in a swathe instead of blowing it up into a wagon. The material was later baled using a flex chamber round baler or a big baler. Hemp yield was estimated in the field and averaged 12 tonnes dry matter per hectare. Weighing of bales showed the losses between calculated and measured harvest to be 34%, which is unacceptable in a crop grown specifically for its biomass. Two main sources of biomass losses were crop stubble and material disintegration by machinery use. However after subtracting these losses, losses of 18% were still unexplained. It is practically impossible to prevent losses at spring harvest because plants are very dry and brittle and the material crumbles easily and falls to the ground. Both the machines tested for cutting the hemp worked well, but there was large difference in their capacity. Both the balers tested worked well, with no differences in capacity or field biomass losses.